Penanaman Nilai-nilai Islam pada Anak-anak Usia Dini Melalui Kegiatan Pengajaran Al-Qur'an di Desa Wakorambu - Riska Riska; Dewi Indriani (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2022)
The purpose of the STIBA Makassar Real Work Lecture (KKN) Batch V is as a form of community service which is a pillar of the Tri Darma of higher education, especially the development of the Al-Qur'an Learning group in Wakorambu village as the main program. The PkM implementation method begins with a field survey and then formulates community needs using the SOAR analysis method, after the analysis was carried out, it was found that a very urgent need was found, namely the development of the TPA group in Wakorambu village. The development of the Wakorambu Village Al-Qur'an Learning was carried out well in accordance with the expected goals.